Long-Covid in Children and Adolescents: Clinical Challenges and Treatment Perspectives - Kornelia Karamus; Rafał Rejamak; Jan Biłogras; Martyna Borowska-Łygan; Konrad Strużek; Wojciech Urban; Jakub Tomaszewski (Journal of Education, Health and Sport)
Introduction: Long COVID is a complication of the coronavirus disease. As a relatively new medical condition, it presents challenges in establishing consistent principles for its classification, diagnosis, and treatment.